(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article explores the importance of the maxim, in politeness theory by examining gender differences in English and Uzbek languages usage patterns. We delve into how both men and women employ the maxim to shed light on subtleties that mirror societal views on gender and politeness. Drawing from conversational analysis data reveals that gender not impacts adherence, to the modesty maxim but also influences how politeness strategies are expressed across diverse cultural settings. The results highlight how language use is influenced by gender and societal expectations in shaping how we communicate. In the study of language and culture, in both English and Uzbek languages lies a focus, on maxims and gender characteristics through the lens of sociolinguistics and politeness theory.